2017
DOI: 10.1038/s41598-017-03012-4
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of Magnetospirillum gryphiswaldense MSR-1 that control cell growth under high-iron and low-oxygen conditions

Abstract: Magnetosome formation by Magnetospirillum gryphiswaldense MSR-1 is dependent on iron and oxygen levels. We used transcriptome to evaluate transcriptional profiles of magnetic and non-magnetic MSR-1 cells cultured under high-iron and low-iron conditions. A total of 80 differentially expressed genes (DEGs) were identified, including 53 upregulated and 27 downregulated under high-iron condition. These DEGs belonged to the functional categories of biological regulation, oxidation-reduction process, and ion binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Moreover, recent work on MSR-1 also suggested that iron can be contained outside magnetite in this strain ( 32 ). Iron-starving conditions can impact the iron cycling and homeostasis in MTB, as low-iron conditions have been shown to induce overexpression of iron acquisition systems in AMB-1 and MSR-1 ( 33 , 34 ). They might optimize the transfer of incorporated iron to magnetosomes for magnetite precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent work on MSR-1 also suggested that iron can be contained outside magnetite in this strain ( 32 ). Iron-starving conditions can impact the iron cycling and homeostasis in MTB, as low-iron conditions have been shown to induce overexpression of iron acquisition systems in AMB-1 and MSR-1 ( 33 , 34 ). They might optimize the transfer of incorporated iron to magnetosomes for magnetite precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, time‐course experiments require to first grow bacteria under iron‐starving conditions ( i.e . no iron provided to the growth medium), which trigger overexpression of iron transporters (Suzuki et al ., 2006; Wang et al ., 2017). This could optimize the transfer of iron to magnetosomes for magnetite precipitation, and prevent accumulation of iron in a reservoir distinct from magnetite.…”
Section: Iron Biomineralization In Mtbmentioning
confidence: 99%
“…Moreover, most of the magnetotactic bacteria strains have been found to consume oxygen, ferric quinate, and nitrate as electron acceptors and use succinate or lactate, acetate, and nitrate as electron donors [11] . Culture medium optimization was very effective for high-yield cultivation of magnetosome, as it has previously been reported that at higher dissolved oxygen (DO) level, cell growth would be greater, but for higher yield of magnetosome, low DO concentrations are the prerequisite [23,24] . Thus, to resolve this situation, it is necessary to enhance DO to an optimum level by stirring the medium to increase the magnetotactic bacteria growth and allow the microbe to lower DO by the respiration process to an optimum level.…”
Section: Introuductionmentioning
confidence: 99%